2012
DOI: 10.1186/1471-2431-12-188
|View full text |Cite
|
Sign up to set email alerts
|

Individual development of preschool children-prevalences and determinants of delays in Germany: a cross-sectional study in Southern Bavaria

Abstract: BackgroundEven minor abnormalities of early child development may have dramatic long term consequences. Accurate prevalence rates for a range of developmental impairments have been difficult to establish. Since related studies have used different methodological approaches, direct comparisons of the prevalence of developmental delays are difficult. The understanding of the key factors affecting child development, especially in preschool aged children remains limited. We used data from school entry examinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
29

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 16 publications
4
12
0
29
Order By: Relevance
“…Studies of other authors showed the prevalence of 24%-27% in children 6-11 years of age 4,8 . A higher prevalence of MND in our study could be explained by the age of the respondents as the deviations are more common in younger children, as indicated in studies by other authors 9 . A research conducted in Holland, also showed a significantly higher prevalence of MND in relation to the general population.…”
Section: Discussionsupporting
confidence: 67%
“…Studies of other authors showed the prevalence of 24%-27% in children 6-11 years of age 4,8 . A higher prevalence of MND in our study could be explained by the age of the respondents as the deviations are more common in younger children, as indicated in studies by other authors 9 . A research conducted in Holland, also showed a significantly higher prevalence of MND in relation to the general population.…”
Section: Discussionsupporting
confidence: 67%
“…With a wider age range, data from the 1995 Australian Health Survey on children aged 0-14 years also showed that boys had a higher prevalence of speech disorders (Keating et al, 2001). Furthermore, a study on 13,182 school beginners in Bavaria, Germany found boys had higher prevalence for all three types of speech impairments: 17.8% vs. 9.5% for pronunciation, 5.1% vs. 2.8% for grammar, and 4.1% vs. 2.0% for rhythm of speech (Stich, Baune, Caniato, Mikolajczyk, & Krä mer, 2012). While it is well documented that more boys than girls have SLD, the underlying mechanisms are unclear.…”
Section: Study (Study Period) Country (Area) Participants Age (Year)mentioning
confidence: 90%
“…Prevalences of single developmental delays were subject to previous analyses in the same District of Bavaria [18,19]. …”
Section: Introductionmentioning
confidence: 99%